2014
DOI: 10.1681/asn.2013040371
|View full text |Cite
|
Sign up to set email alerts
|

Nephropathy and Elevated BP in Mice with Podocyte-Specific NADPH Oxidase 5 Expression

Abstract: NADPH oxidase (Nox) enzymes are a significant source of reactive oxygen species, which contribute to glomerular podocyte dysfunction. Although studies have implicated Nox1, -2, and -4 in several glomerulopathies, including diabetic nephropathy, little is known regarding the role of Nox5 in this context. We examined Nox5 expression and regulation in kidney biopsies from diabetic patients, cultured human podocytes, and a novel mouse model. Nox5 expression increased in human diabetic glomeruli compared with nondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
125
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 54 publications
6
125
1
1
Order By: Relevance
“…Nox5 expression is increased in human atherosclerotic and aneurysm lesions26, 27 and in kidneys from diabetic patients 28. We demonstrated that mice expressing human Nox5 in a podocyte‐specific manner exhibit podocyte injury and renal dysfunction,28 and that human Nox5 expression in mesangial cells causes renal fibrosis, nephropathy, and exacerbated atherosclerosis in diabetic mice 29. Findings from recent genome wide‐association studies of 475 000 individuals identified Nox5 as a candidate blood pressure–associated gene 30.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Nox5 expression is increased in human atherosclerotic and aneurysm lesions26, 27 and in kidneys from diabetic patients 28. We demonstrated that mice expressing human Nox5 in a podocyte‐specific manner exhibit podocyte injury and renal dysfunction,28 and that human Nox5 expression in mesangial cells causes renal fibrosis, nephropathy, and exacerbated atherosclerosis in diabetic mice 29. Findings from recent genome wide‐association studies of 475 000 individuals identified Nox5 as a candidate blood pressure–associated gene 30.…”
mentioning
confidence: 79%
“…Nox5 is expressed in all vascular cell types, including endothelial cells, VSMCs, and perivascular adventitial fibroblast,12, 14, 24 and plays a role in angiotensin II (Ang II)‐ and endothelin‐1 (ET‐1)‐mediated redox signaling 25. Nox5 expression is increased in human atherosclerotic and aneurysm lesions26, 27 and in kidneys from diabetic patients 28. We demonstrated that mice expressing human Nox5 in a podocyte‐specific manner exhibit podocyte injury and renal dysfunction,28 and that human Nox5 expression in mesangial cells causes renal fibrosis, nephropathy, and exacerbated atherosclerosis in diabetic mice 29.…”
mentioning
confidence: 99%
“…Urinary 8-isoprostanes is expressed as picograms per 24 h. Urinary 8-hydroxy-2′-deoxyguanosine ELISA A urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) enzyme immunoassay kit (StressMarq Biosciences Victoria, BC, Canada) was used to measure 8-OHdG in urine, as described by the manufacturer. Urinary 8-OHdG is expressed as nanograms per 24 h. Lucigenin assays Glomerular fractions obtained from the frozen renal cortices of the different experimental groups were harvested in 100 μl ice-cold phosphate buffer (50 mmol/l KH 2 PO 4 , 1 mmol/l EGTA and 150 mmol/l sucrose; pH 7.4) with protease inhibitors, as previously described [11]. Baseline activity was measured by adding 50 μl glomerular extract to 175 μl buffer and 2.5 μl 1 mmol/l lucigenin (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Among the seven members of the NOX family, NOX1, NOX2 (also named gp91 phox ), and NOX4 are expressed in kidneys of humans and mice, whereas NOX5 is expressed only in humans. [1][2][3][4][5] We have been examining the role of NOX isoforms in diabetic kidney disease (DKD) and we recently found that NOX2 did not play a major role in mediating DKD with type 1 diabetes. 1,6 However, NOX4 was upregulated in the NOX2 knockout (KO) diabetic kidney, particularly in glomeruli and podocytes, and thus may play a prominent role.…”
mentioning
confidence: 99%